MADRASAH EDUCATION PATTERNS IN BOARDING SCHOOL (CASE STUDY AT NURUL ISLAM BOARDING SCHOOL ANTIROGO JEMBER) - Sofyan Hadi; Bambang Eko Aditia (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
In the early twentieth century, pesantren developed madrasah education as a response to the colonial Dutch education system. Pesantren adopted formal instructional systems while maintaining their traditional characteristics, particularly the study of classical Islamic texts. This study aims to examine the process of establishment, management practices, curriculum, and student development programs of madrasah education at Pesantren Nurul Islam Jember. This research employs a qualitative method with a phenomenological approach and a case study design. Data were collected through observation, interviews, and documentation, while data analysis used the interactive model proposed by Miles and Huberman. The findings indicate that Pesantren Nurul Islam Jember originated from the establishment of the Nurul Islam Jember Islamic Education Foundation in 1985 and later developed into an integrated pesantren with collective leadership based on modern management principles. The curriculum implemented is an integrated curriculum encompassing religious, moral, general, and skills education through a combination of traditional and modern learning methods. Student development programs are carried out synergistically through the roles of the board of trustees, guidance and counseling services, student organizations, and institutional regulations. This study is expected to contribute both academically and practically to the development of pesantren education.